2014
DOI: 10.3122/jabfm.2014.01.130002
|View full text |Cite
|
Sign up to set email alerts
|

Staff versus Physician Vaccine Protocols for Influenza Immunization During Pregnancy

Abstract: Background: Pregnant women and their fetuses are known to be at increased risk for influenza-associated morbidity and mortality. The Advisory Committee on Immunization Practices and others have recommended influenza vaccination for all pregnant women at any gestational age, but vaccination rates for pregnant women remain low, near 45%.Methods: A retrospective chart review was performed at each of 4 sites during the 2010 to 2011 and 2011 to 2012 influenza seasons to examine the rates of flu vaccination offering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…As described above, Ogburn et al saw an increase from 3% during the first year of the intervention to 37% in the season in which standing orders were incorporated [70]. Zakrzewski et al did not implemental a standard standing order protocol but evaluated the impact of a nurse-driven recommendation protocol compared to a provider-driven recommendation protocol and found limited difference between the two [71].…”
Section: Standing Orders-standing Orders For Vaccination Represent a mentioning
confidence: 99%
“…As described above, Ogburn et al saw an increase from 3% during the first year of the intervention to 37% in the season in which standing orders were incorporated [70]. Zakrzewski et al did not implemental a standard standing order protocol but evaluated the impact of a nurse-driven recommendation protocol compared to a provider-driven recommendation protocol and found limited difference between the two [71].…”
Section: Standing Orders-standing Orders For Vaccination Represent a mentioning
confidence: 99%
“…Interview topics were specific to maternal influenza and Tdap vaccination including office policies and procedures, provider and nurse efforts to increase rates, previous quality improvement (QI) initiatives, perceived barriers and facilitators. Interview topics and discussion guides were based on our related studies (Rand et al, 2020 ) and other maternal vaccination studies (Ault et al, 2012 ; Mouzoon et al, 2010 ; Zakrzewski et al, 2014 ). The interview guide was piloted, and suggested prompts continued to be refined after piloting.…”
Section: Methodsmentioning
confidence: 99%
“…With an observational study, Zakrzewski et al 8 observed that the flu vaccine was less likely to be given to pregnant patients when initiated through a medical assistant-or nurse-driven protocol than a physician-based protocol, even though the vaccine was more frequently offered by nurses or medical assistants. Simply offering the vaccine is insufficient.…”
Section: Research By Family Physicians For Family Physicians Can Imprmentioning
confidence: 99%